(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
This paper discussed the challenges of human resource development as it relates with respect to counselling education in College of Arabic and Islamic legal studies, and its attendant effects in the production of well-rounded graduates, prepared for every facet of life. It also considered the History of Guidance and Counselling in Nigeria and History of College of Arabic and Islamic Legal Studies. A look at the Nigerian system of education shows that counselling education has taken off in most Colleges (institutions) but Counselling unit is yet to take off, for effective counselling programme in the College. If the unit is established, this will go a long way in enhancing human resource development in Kwara State College of Arabic and Islamic Legal studies, Ilorin.